Factors Affecting The Management Of Income - Nur Elian Rahma Rucita; Riki Sanjaya (Kesatuan Press, 2021)
This research aims to obtain empirical evidence about the effect of institutional ownership, managerial ownership, board of commissioner frequency meeting, audit committee frequency meeting, firm size, leverage, audit quality and independent commissioner to earning management. The company used this research is manufacturing company listed in Indonesia Stock Exchange during 2017-2019. There are 37 companies and 111 amounts of data that the meet criteria using purposive sampling method. The model of research used multiple regression analysis. The result shows that leverage influence earning management. Other independent variables institusional ownership, managerial ownership, board of commissioner frequency meeting, audit committee frequency meeting, firm size, audit quality and independent commissioner have no effect to earning management.